FAKTOR YANG MEMOTIVASI PRESTASI KERJA KARYAWAN MARKETING PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. KANTOR WILAYAH MAKASSAR - Megawaty Megawaty (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine and analyze the factors that motivate the performance of marketingPT employees. Bank Negara Indonesia (Persero) Tbk Makassar Regional Office. Data analysis used is quantitative descriptive analysis method that is mean statistic and instrument analysis consist of validity test and reliability test with tool of IBM SPSS Version 21.0. The results showed that the factors that motivate the performance of marketing employees of PT. Bank Negara Indonesia (Persero) Tbk Makassar Regional Office in the form of interest factor which is dominant factor, requirement factor, standard to be achieved, ability, task and challenging situation, expectation and confidence, and situation of competition.